Digitising newspaper content in Indonesia: the challenge of enforcing the culture of immediacy - Priyonggo, Ambang; Hamedi Mohd Adnan (Penerbit Universiti Kebangsaan Malaysia, 2021)
This research is aimed at examining how the culture of immediacy is implemented in a newspaper undergoing digital transformation. This paper is written based on the case of Harian Kompas, the most influential newspaper in Indonesia, that just officially launched its paywall-based digital site, kompas.id as an alternative platform. Within this context, the daily implemented the digital-first strategy to put the priority of rapid digital news production prior to its slow-pace print edition. Through ethnography fieldwork in the daily’s newsroom, relying on in-depth interviews and participant observations, the study highlights a notion that the culture of immediacy is not easy to implement. The challenge rests on the fact that it is not only contradictory to the common rhythm of rigid newspaper work-flow and deadline among reporters and editors, but further it is considered harmful to the daily’s prescribed core value of comprehensive journalism originated from its editorial philosophy as well as journalism credo of being credible. It is within the constant negotiations among all the newsroom’s actors, the culture of immediacy remains to be a contesting value that should be carried out by the daily as a way to excrete the old habit of print deadline while the digital-first transformation is still taking shape.